2021
DOI: 10.3389/fpsyg.2021.680614
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated With Burnout of Frontline Healthcare Workers in Fighting Against the COVID-19 Pandemic: Evidence From China

Abstract: ObjectivesThe sudden outbreak of the novel coronavirus disease (COVID-19) plunged healthcare workers (HCWs) into warfare. This study aimed to determine the prevalence of burnout and the factors associated with it among frontline HCWs fighting COVID-19.MethodsA cross-sectional survey was conducted among frontline HCWs fighting against the COVID-19 in Wuhan, Harbin, and Shenzhen during the period from February 18 to March 4. Finally, HCWs were recruited using cluster sampling, 1,163 HCWs were included in the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 65 publications
1
38
2
1
Order By: Relevance
“…However, upon comparing the results from periods 1 and 3, similar tendencies were observed; nurses and those in EICU tended to have higher odds of burnout than their counterparts. While there are mixed results concerning risk factors for burnout during the COVID-19 pandemic, some literature reported that nurses were more vulnerable to burnout than physicians, especially in ICU settings [ 21 , 24 , 26 , 32 ]. Given that nurses are always working in the frontline of patient care throughout their shifts, the results were as expected, and hospital administrators may need to focus on nurses to prevent burnout with measures such as occupational mental health surveillance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, upon comparing the results from periods 1 and 3, similar tendencies were observed; nurses and those in EICU tended to have higher odds of burnout than their counterparts. While there are mixed results concerning risk factors for burnout during the COVID-19 pandemic, some literature reported that nurses were more vulnerable to burnout than physicians, especially in ICU settings [ 21 , 24 , 26 , 32 ]. Given that nurses are always working in the frontline of patient care throughout their shifts, the results were as expected, and hospital administrators may need to focus on nurses to prevent burnout with measures such as occupational mental health surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…It needs to be noted that HCWs are vulnerable to burnout at the baseline, with reported prevalence in Japan around 20–30% before the COVID-19 pandemic [ 11 , 12 ]. So far, studies have reported that the prevalence of burnout among HCWs has further increased in various countries during the pandemic [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. A recent systematic review and meta-analysis that quantified the psychological symptoms among frontline HCWs during pandemics noted that the prevalence of burnout was 31.8% [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A rising number of nurses were infected with SARS-CoV-2 or died in the line of duty [27,28]. Additionally, many health care facilities experienced serious problems, such as poor planning, preparation, organisation, and leadership, and the failure to ensure adequate stocks of medical supplies, including personal protective equipment for medical staff [28][29][30]. The challenges resulting from the pandemic have exacerbated the already existing crisis in nursing worldwide and increased the possibility of phenomena related to occupational burnout or bullying.…”
Section: Discussionmentioning
confidence: 99%
“…According to the current study, the finding suggested that 32.2% of the participants had hours/week more than 40 hours/week, indicating that nearly a third of the participants had complained the long working hours during the controlled COVID-19 period. In this stage, Chinese nurses are facing various huge challenges, such as increased the long working hours, extra effort, heavily workload, stress, new risk, and so on ( 20 , 53 ). Except for front-line wards nurses, the majority of Chinese nurse's salary did not increase due to decreased hospital economic benefit during a fight against the COVID-19 epidemic period, which contributes to the effort-reward imbalance at work being more serious.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, another survey conducted in China showed that nurses who worked in COVID-19 wards had lower burnout symptom than those worked in usual wards ( 19 ). The generalizability of findings regarding the prevalence of burnout is inconsistent, since the study was conducted on different stages of the COVID-19 epidemic, and a convenience sample of participating by social media, and varied working demands ( 20 , 21 ). Therefore, this study believes that the prevalence of burnout of Chinese nurses is of worry and needs to be assessed further during different stages of the COVID-19 epidemic.…”
Section: Introductionmentioning
confidence: 99%